Neutrophil gelatinase–associated lipocalin (NGAL): a promising biomarker for the early diagnosis of acute kidney injury (AKI) - Antonucci, Elio; Lippi, Giuseppe; Ticinesi, Andrea; Pigna, Federica; Guida, Loredana; Morelli, Ilaria; Nouvenne, Antonio; Borghi, Loris; Meschi, Tiziana (Acta Biomedica Atenei Parmensis, 2014)
Acute kidney injury (AKI) is a common complication that occurs in a broad spectrum of clinical settings. Cardiac surgery-associated AKI continues to be a well-recognized complication of cardiac surgery with high morbidity and mortality. The lack of early biomarkers has for long prevented timely interventions to mitigate the effects of AKI. Serum creatinine is not a timely marker of AKI, so that it cannot be used to set potentially effective therapies to treat AKI in patients during phases when the injury is still potentially reversible. Neutrophil gelatinase–associated lipocalin (NGAL) has been identified as a promising biomarker for early detection of AKI. Several studies have shown that NGAL levels significantly increase in AKI patients 24 to 48 hours before a detectable increase of serum creatinine. Recent studies also suggest that measurements of urinary NGAL levels in patients at risk for cardiac surgery–associated AKI may facilitate its early diagnosis and allow clinicians to implement therapeutic adjustments that have the potential to reverse renal cellular damage and minimize further kidney injury.